Utilization of Android Applications in Helping Culinary SMEs in Palembang City to Increase Sales: Pemanfaatan Aplikasi Android dalam Membantu UMKM Kuliner di Kota Palembang Untuk Meningkatkan Penjualan - Paray Theo Lonando (IKesT Muhammadiyah Palembang, 2025)
Digitalization has brought significant changes in various economic sectors, including the culinary industry. This study aims to analyze the use of Android applications in helping culinary Micro, Small, and Medium Enterprises (MSMEs) in Palembang City increase sales. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observations, and literature studies. The results of the study show that 80% of culinary MSMEs in Palembang have used Android-based applications, such as food delivery services (GoFood, GrabFood, ShopeeFood), digital cashier applications (Moka POS, Pawoon, Majoo), and social media and e-commerce (Instagram, WhatsApp Business, Tokopedia). The use of Android applications has been proven to have a positive impact on increasing turnover by up to 50% in the first six months, increasing operational efficiency, and expanding market reach. However, challenges such as high commission costs, lack of digital literacy, and tight competition are still the main obstacles for culinary MSMEs in optimizing digital technology. To overcome these obstacles, digital training, government support, and more innovative marketing strategies are needed. By optimally utilizing Android applications, culinary MSMEs in Palembang City have great opportunities to develop and compete in the digital era